1999
DOI: 10.1530/jrf.0.1160373
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride content of bovine oocytes and early embryos

Abstract: A microfluorescence technique was used to measure the triglyceride content of a minimum of two bovine oocytes or preimplantation embryos up to the hatched blastocyst stage. Embryos were produced in vitro from abattoir-derived ovaries and grown in medium containing synthetic oviductal fluid, amino acids and BSA (SOFaaBSA medium); 10% fetal calf serum was added to some of the embryos at the four-cell stage. Before maturation, the triglyceride content of oocytes was 59 +/- 1.37 ng and it decreased (P < 0.05) afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
134
1
6

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(152 citation statements)
references
References 0 publications
11
134
1
6
Order By: Relevance
“…Lipid accumulation was found and quantified from day 4 of development until the blastocyst stage of embryos cultured with serum [21]. Further, in the blastocyst stage of bovine embryos, the relative abundance of mRNA for lipidogenics genes increased regarding the previous stages [4].…”
Section: Alternative Mechanism For Lipid Accumulationmentioning
confidence: 97%
See 3 more Smart Citations
“…Lipid accumulation was found and quantified from day 4 of development until the blastocyst stage of embryos cultured with serum [21]. Further, in the blastocyst stage of bovine embryos, the relative abundance of mRNA for lipidogenics genes increased regarding the previous stages [4].…”
Section: Alternative Mechanism For Lipid Accumulationmentioning
confidence: 97%
“…Neither did Crosier et al [15], with the same kind of serum and a similar technique used by us to quantify, studying the morula stage. However, on day 4 of embryos cultured with serum since day 2 (9-16 cells), Ferguson and Leese [21], observed that the triglyceride content increases in regard to the previous days and to the same stage without serum. Although the technique used by us to quantify lipids might not have been sensitive enough to detect the accumulation such as the one used by Ferguson and Leese [21], it is possible that 10 % v/v of fetal serum used by them generate earlier accumulation than the 5 % v/v estrous serum used by us and Crosier et al [15].…”
Section: Lipidsmentioning
confidence: 98%
See 2 more Smart Citations
“…Fatty acids are an endogenous source of energy during oocyte maturation; several lines of evidence support the idea of fatty-acid oxidation as a source of essential ATP for oocyte maturation and for early development of the embryo. For example, the triglyceride content of the bovine oocytes decreased during in vitro maturation (IVM), as well as after fertilization (Ferguson and Leese, 1999). In addition, lipase activity was increased in the bovine oocytes following IVM (Cetica et al, 2002).…”
Section: Nefasmentioning
confidence: 99%